Strategies to manage volatility in ports (container ports) - Sia, Clement Yong Sheng (Nanyang Technological University, 2022)
Black swan event such as the COVID-19 pandemic has greatly affected port operations. Container ports are challenged by port congestion volatilities, which is resulted from many factors such as shortage of labour and truck availability to cope with the surge of incoming containers into the port. This contributed to the delays in vessel turnaround time and increased port stay duration. Accumulation of containers due to shipment backlogs has led to an imbalance in empty containers distributed across the ports. Over the years, the growing size of vessels presents a diseconomy of scale to ports where port capacity is not able to meet the unexpected surge in the supply of containers due to limited berths and yard space. The variability in the number of port calls affects the reliability of the vessel schedule. Thus, it is of paramount importance that ports select suitable strategies to tackle port congestion volatility. Strategies discussed in this report include Engagement with port stakeholders on managing cargo flow, Optimization of port capacity, and Facilitating Decision making with information technology. This report aims to recommend suitable strategies for ports to tackle uncertainties in a volatile environment. It will provide helpful insights to the port users and operators. This report explores the use of the Analytic Hierarchy Process model for the decision-making of port coping strategies on port congestion volatility. The results include quantitative data about the weights of each criteria which will be used to determine how important is the strategy. Discussion and analysis cover the relevant insights into the strategies.